2019
DOI: 10.1177/2045894019886249
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endarterectomy in a 12‐year‐old boy with multiple comorbidities

Abstract: A 10-year-old boy, with multiple comorbidities presented with fever, exertional dyspnea, fatigue and an obliterated brachiocephalic and inferior caval vein. Chronic thromboembolic pulmonary hypertension (CTEPH) was diagnosed. Nadroparine, antibiotics and supplemental oxygen were successfully started. Aged 12 years, supplemental oxygen was permanently needed with progressive exertional dyspnea and fatigue. In the country of residence the patient was considered as inoperable. The right ventricle was severely dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The successful management of our patient by PEA required a multi-disciplinary team, including cardiac surgeons, hematologists, cardiac intensivists, and cardiologists. Furthermore, this case, along with other cases reported in the literature [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], demonstrate that young age is not a contraindication for PEA, and this may be the single most effective treatment for acute cor pulmonale due to massive PE when the thrombus is not resolved with standard anticoagulation and anti-thrombolytic therapy.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The successful management of our patient by PEA required a multi-disciplinary team, including cardiac surgeons, hematologists, cardiac intensivists, and cardiologists. Furthermore, this case, along with other cases reported in the literature [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], demonstrate that young age is not a contraindication for PEA, and this may be the single most effective treatment for acute cor pulmonale due to massive PE when the thrombus is not resolved with standard anticoagulation and anti-thrombolytic therapy.…”
Section: Discussionsupporting
confidence: 63%
“…To our knowledge, this is the first case of PEA in a child developing acute cor pulmonale due to massive PE associated with NS. Prior published reports have demonstrated that PEA is feasible and well tolerated to relieve acute PE secondary to different comorbidities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Madani et al have shown that after PEA, there was a significant improvement in hemodynamics, RV function, and the functional status of patients with minimal postoperative complications and low perioperative mortality, similar to that reported for adults with CTEPH, with the notable exception being a higher rate of re-thrombosis in pediatric patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was noted to have unexplained PH on routine screening echocardiography in the setting of a chronic hypercoagulable state and recent RA thrombus associated with a central venous catheter, and his diagnosis was confirmed by lung VQ scan and right heart catheterization. While a recently published case report described a 12-year-old with CTEPH successfully treated with PTE, that patient had severe comorbidities including paraplegia, and he was found to have factor V Leiden and antiphospholipid antibodies during his hypercoagulable workup (11).…”
Section: Discussionmentioning
confidence: 99%
“…While CTEPH is a rare disease in adults, it is quite exceptional in the paediatric population. There are very little data published on chronic thromboembolism and only few case reports/series with CTEPH [208][209][210]. This important knowledge gap should be addressed by international prospective registries.…”
Section: Paediatric Ctephmentioning
confidence: 99%